Application of avidin-biotin technology and adsorptive transfer stripping square-wave voltammetry for detection of DNA hybridization and avidin in transgenic avidin maize - Masarik, Michal; Kizek, Rene; Kramer, Karl J; Billova, Sabina; Brazdova, Marie; Vacek, Jan; Bailey, Michele; Jelen, Frantisek; Howard, John A (Analytical chemistry, 2003)
The proteins streptavidin and avidin were electrochemically detected in solution by adsorptive transfer stripping square wave voltammetry (AdTS SWV) at a carbon paste electrode (CPE). AdTS SWV was used to quantify biotinylated oligonucleotides, DNA hybridizations, and avidin in extracts of transgenic avidin maize. The detection limits of denatured and native streptavidin were 6 pM and 120 nM, respectively. The results demonstrated that streptavidin/avidin AdTS SWV is a sensitive and specific method for quantifying DNA and proteins in biological samples such as foods and tissue extracts, including genetically modified crops (avidin maize) and other plants in neighboring fields.
Keywords: Adsorption; biotin; adsorpce; avidin; hybridizace nukleových kyselin; elektrody; geneticky modifikované rostliny; Zea mays; Biotin; streptavidin; Streptavidin; DNA; Plants, Genetically Modified; Electrodes; kukuřice setá; Nucleic Acid Hybridization; Electrochemistry; Avidin; elektrochemie